2000
DOI: 10.1641/0006-3568(2000)050[0521:scanop]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Cultivation: A New Old Paradigm for Managing Tropical Forests

Abstract: ) are senior fell ows in envi ro n m en t a l s tu d i e s , Ea s t-West Cen ter, Ho n ol u l u , and Ngh i em Phuong Tuyen (email: tuyen @ u plands.ac.vn) are re se a rch ers at, and Le Trong Cuc (em a i l :c u c @ u plands.ac.vn) is dire ctor of , the Cen ter for Re sou rce and Envi ro n m ental Stu d i e s , Vi etnam Na tional Un ivers i ty, Ha n o i , 1 6 7 Bui Thi Xu a n , Ha n o i , Vi etn a m . Step h en Lei sz (e-mail: s j lv m @ f pt.vn) is GIS/monito ring and eva l u a tion advi so r, C A R E In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(125 citation statements)
references
References 21 publications
2
115
0
8
Order By: Relevance
“…This is because agroforestry farms have a good supply of firewood, and relatively higher farm income allowing a larger proportion of agroforestry farmers to buy gas cylinders. Recent studies in different locations around the tropics indicate that one important reason for deforestation is crop growing (Babigumira et al 2014), and swidden farming is often held to be the principle driving force for that (Fox et al 2000;Angelsen 1995;Myers 1992). However, Heltberg et al (2000) reported that one of the main drivers of forest degradation in rural India is unsustainable firewood collection.…”
Section: Resultsmentioning
confidence: 99%
“…This is because agroforestry farms have a good supply of firewood, and relatively higher farm income allowing a larger proportion of agroforestry farmers to buy gas cylinders. Recent studies in different locations around the tropics indicate that one important reason for deforestation is crop growing (Babigumira et al 2014), and swidden farming is often held to be the principle driving force for that (Fox et al 2000;Angelsen 1995;Myers 1992). However, Heltberg et al (2000) reported that one of the main drivers of forest degradation in rural India is unsustainable firewood collection.…”
Section: Resultsmentioning
confidence: 99%
“…Nas duas últimas décadas, essa expansão tem recebido grande atenção devido ao seu papel no desflorestamento das regiões tropicais (Skole et al, 1994;Angelsen, 1995;Brady, 1996;Brown e Schreckenberg, 1998), na perda de biodiversidade (de Jong, 1997) e no aquecimento global (Fearnside e Guimarães, 1996;Tinker et al, 1996;Fox et al, 2000). Por outro lado, muitos estudos vêm demonstrando que a interferência humana no processo sucessional da floresta, por meio das atividades agrícolas, acaba funcionando como fonte de variabilidade, mantendo ou mesmo promovendo a biodiversidade regional (Andrade e Rubio-Torgler, 1994;Neves, 1995;Raman et al, 1998;Steinberg, 1998;Moguel e Toledo, 1999;Altieri, 1999;Gupta, 2000).…”
Section: A Agricultura De Corte E Queimaunclassified
“…Continuously rising demands for crop land and timber have led to substantial deforestation in many regions (Drigo, 2005), and although the global tropical deforestation rate remains high at 13 Mha yr −1 (FAO, 2006), forest regrowth on abandoned agricultural land is increasing, particularly in Latin America (Aide and Grau, 2004;Hecht, 2010) and South East Asia (cf. Fox et al, 2000;Xu et al, …”
Section: Introductionmentioning
confidence: 99%